MicroRNA-targeting in male infertility: Sperm microRNA-19a/b-3p and its spermatogenesis related transcripts content in men with oligoasthenozoospermia - Abu-Halima, Masood; Becker, Lea Simone; Ayesh, Basim M.; Meese, Eckart (Frontiers in Cell and Developmental Biology, 2022)
Objective: To elucidate and validate the potential regulatory function of miR-19a/b-3p and its spermatogenesis-related transcripts content in sperm samples collected from men with oligoasthenozoospermia. Methods: Men presenting at an infertility clinic were enrolled. MicroRNA (miRNA) and target genes evaluation were carried out using in silico prediction analysis, Reverse transcription-quantitative PCR (RT-qPCR) validation and Western blot confirmation. Results: The expression levels of miRNA-19a/b-3p were significantly up-regulated and 51 target genes were significantly down-regulated in oligoasthenozoospermic men compared with age-matched normozoospermic men as determined by RT-qPCR. Correlation analysis highlighted that sperm count, motility, and morphology were negatively correlated with miRNA-19a/b-3p and positively correlated with the lower expression level of 51 significantly identified target genes. Furthermore, an inverse correlation between higher expression levels of miRNA-19a/b-3p and lower expression levels of 51 target genes was observed. Consistent with the results of the RT-qPCR, a reduced expression levels of STK33 and DNAI1 protein levels were identified in an independent cohort of sperm samples collected from men with oligoasthenozoospermia. Conclusion: Findings suggest that the higher expression of miRNA-19a/b-3p or the lower expression of target genes are associated with oligoasthenozoospermia and male infertility, probably through influencing basic semen parameters. This study lay the groundwork for future studies focused on investigating therapies for male infertility.